2004
DOI: 10.1038/sj.bjc.6602184
|View full text |Cite
|
Sign up to set email alerts
|

Expression and co-expression of the members of the epidermal growth factor receptor (EGFR) family in invasive breast carcinoma

Abstract: The epidermal growth factor receptor (EGFR) family plays an important role in breast carcinogenesis. Much interest has been focused recently on its members because of their potential role as prognostic indicators in breast cancer and their involvement in cancer therapy. We have evaluated more than 1500 cases of invasive breast carcinoma immunohistochemically using tissue microarray technology to examine the expression of EGFR family receptor proteins. We have found that 20.1 and 31.8% of cases were positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
219
7
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(252 citation statements)
references
References 43 publications
25
219
7
1
Order By: Relevance
“…This has led to a more 'clinically acceptable' classification, with the proportion of HER2-positive patients ranging between 12.5% and 15% and the total number of unclassified patients being only 3.5% of the available cases. The distribution and percentages of breast cancer patients into the three big classes of luminal, basal and HER2 were established in a seminal study by Sorlie et al [6] and confirmed by subsequent papers [52][53][54]. The method described here has produced a breast cancer classification consistent with the proportion of cancer subtypes reported in other studies.…”
Section: Discussionsupporting
confidence: 72%
“…This has led to a more 'clinically acceptable' classification, with the proportion of HER2-positive patients ranging between 12.5% and 15% and the total number of unclassified patients being only 3.5% of the available cases. The distribution and percentages of breast cancer patients into the three big classes of luminal, basal and HER2 were established in a seminal study by Sorlie et al [6] and confirmed by subsequent papers [52][53][54]. The method described here has produced a breast cancer classification consistent with the proportion of cancer subtypes reported in other studies.…”
Section: Discussionsupporting
confidence: 72%
“…Several reports, based mainly on the expression of HER1 and HER2, demonstrate that the EGF family of receptors are involved in poor prognosis in various cancers including bladder cancer (Lonn et al, 1995;Arpino et al, 2004;Blackwell et al, 2004;Popov et al, 2004). In contrast to HER1 and HER2, our study on bladder tumours (Memon et al, 2004) and other studies on breast tumours (Abd El-Rehim et al, 2004) have suggested that increased expression of HER3 and HER4 is associated with improved survival. This is supported by data on cancer cells that demonstrate a ligand-dependent proapoptotic function of the HER4-expressing cells (Sartor et al, 2001).…”
Section: Discussionsupporting
confidence: 41%
“…This study included 31 biomarkers of clinical and biological relevance to BC tumourigenesis and progression [9,11] Primary Breast Carcinoma series previously studied using gene expression profiling [14].…”
Section: Patients and Tumoursmentioning
confidence: 99%